Conservation of land plant-specific receptor-like cytoplasmic kinase subfamily XI possessing a unique kinase insert domain - Yayen, Joseph; Chan, Ching; Sun, Ching-Mei; Chiang, Su-Fen; Chiou, Tzyy-Jen (Frontiers in Plant Science, 2023)
The number of genes encoding receptor-like kinases (RLKs) has expanded in the plant lineage. Their expansion has resulted in the emergence of diverse domain architectures that function in signaling cascades related to growth, development, and stress response. In this study, we focused on the receptor-like cytoplasmic kinase subfamily XI (RLCK XI) in plants. We discovered an exceptionally long kinase insert domain (KID), averaging 280 amino acids, between subdomains VII and VIII of the conserved protein kinase domain. Using sequence homology search, we identified members of RLCK XI with the unique KID architecture in terrestrial plants, up to a single copy in several hornwort and liverwort species. The KID shows a high propensity for being disordered, resembling the activation segment in the model kinase domain. Several conserved sequence motifs were annotated along the length of the KID. Of note, the KID harbors repetitive nuclear localization signals capable of mediating RLCK XI translocation from plasma membranes to the nucleus. The possible physiological implication of dual localization of RLCK XI members is discussed. The unique domain architecture of RLCK XI represents a newfound family among plant RLKs specific to land plants.